The Contribution of AI in Writing Scientific Articles in Higher Education Environments: contribution of AI - Muslimin; Ilham; Hamsaturrahman (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to analyze the contribution of Artificial Intelligence (AI) in writing academic scientific articles in universities. This study uses a qualitative descriptive approach. The subjects of this study were 54 respondents consisting of 39% lecturers and 61% students in Mataram City, Lombok, Indonesia. Data was obtained through questionnaires and analyzed using an interactive model that included reduction, presentation, and conclusion drawing. In addition, data source triangulation was used to consider the validity and credibility of the data used. The results showed that AI contributed positively to improving writing quality, time efficiency, and academic productivity. Platforms such as ChatGPT with a usage percentage of 30%, Grammarly 9%, QuillBot 5%, Meta AI 7%, Cici AI 1%, and others 12%, have been proven to assist in literature search/preference with a presentation of 35%, writing framework preparation (23%), idea or argument development (16%), followed by text paraphrasing (13%), language checking (12), and other uses (11%). The conclusion of this study is that the use of AI has had a significant impact on the transformation of scientific writing practices among lecturers and students. AI acts not only as a technical tool, but also as a cognitive partner that accelerates, enriches, and streamlines the academic writing process in higher education.